Acute Care Use for Ambulatory Care–Sensitive Conditions in High-Cost Users of Medical Care with Mental Illness and Addictions. (December 2018) - Hensel, Jennifer M.; Taylor, Valerie H.; Fung, Kinwah; Yang, Rebecca; Vigod, Simone N.
Objective: The role of mental illness and addiction in acute care use for chronic medical conditions that are sensitive to ambulatory care management requires focussed attention. This study examines how mental illness or addiction affects risk for repeat hospitalization and/or emergency department use for ambulatory care–sensitive conditions (ACSCs) among high-cost users of medical care. Method: A retrospective, population-based cohort study using data from Ontario, Canada. Among the top 10% of medical care users ranked by cost, we determined rates of any and repeat care use (hospitalizations and emergency department [ED] visits) between April 1, 2011, and March 31, 2012, for 14 consensus established ACSCs and compared them between those with and without diagnosed mental illness or addiction during the 2 years prior. Risk ratios were adjusted (aRR) for age, sex, residence, and income quintile. Results: Among 314, 936 high-cost users, 35.9% had a mental illness or addiction. Compared to those without, individuals with mental illness or addiction were more likely to have an ED visit or hospitalization for any ACSC (22.8% vs. 19.6%; aRR, 1.21; 95% confidence interval [CI], 1.20-1.23). They were also more likely to have repeat ED visits or hospitalizations for the same ACSC (6.2% vs. 4.4% of those without; aRR, 1.48; 95% CI, 1.44-1.53). These associations were stronger in stratifications by mental illness diagnostic subgroup, particularly for those with a major mental illness. Conclusions: The presence of mental illness and addiction among high-cost users of medical services may represent an unmet need for quality ambulatory and primary care.